EVALUATION OF RESIN/SILICONE BASED ROOT CANAL SEALERS. PART I: PHYSICAL PROPERTIES - (:unkn) unknown (INST MATERIALS PHYSICS, 2012)
The aim of this study was to evaluate the physical properties of EndoRez, Diaket, Epiphany, Roekoseal, Fibrefill, GuttaFlow, AHPlus, AH26 to that of a traditional zinc oxide based Kerr PCS sealers. Ten samples of each material were evaluated for flow, radiopacity, solubility and dimensional change tests according to ISO standards 2001-6876. The findings were statistically analyzed. Radiopacity and solubility of all sealers were in accordance with ISO standards 6876, except dimensional stability. However, all sealers had expansion values above the ISO requirements. Epiphany sealer showed the greatest expansion and the most flow rates under the given condition (p<0.05). AH26 sealer was found to be the most soluble sealer (p<0.05). Although AHPlus sealer was found to be the most radiopaque sealer, the difference was not significant between AHPlus and Roekoseal, Epiphany and Kerr PCS (p>0.05). According to the result of this study, all root canal sealers showed acceptable properties due to ISO standards except dimensional stability.
Keywords: Root canal sealer; Flow; Radiopacity; Solubility; Dimensional changes; ENDODONTIC SEALERS; GUTTA-PERCHA; RADIOPACITY; FLOW; ADHESION; PASTES; DENTIN; FILM